The association between perception of esthetics and gingivitis in intermediate school students in Dammam, Saudi Arabia - Abdulaziz Almutair; Abdulrahman Alhumaidan; Hassan Almoghawi; Khalid Alfadhli; Mohammed Nazir; Khalifa Al-Khalifa (Elsevier, 2019)
Introduction: Gingivitis is a common clinical condition characterized by swelling, redness, and bleeding at the gums and it is described as an inflammatory reaction. Esthetics is an important aspect that can affect the quality of patient's life. However, it is not known if the perception of esthetic can affect patient's gingival health. Objective: The present study was designed to assess the relationship between the perception of esthetic and gingivitis in a population of intermediate school students in Dammam, Saudi Arabia. Material & methods: A cross-sectional study was conducted at the public intermediate schools in Dammam in the form of a questionnaire. An oral examination to record gingival index was also used in this study. The study population consisted of students (11-19 years old). The sample size was 1638 students. The subjects with disabilities or special needs were excluded from the study. Schools were stratified by gender and randomly selected. The students in each school were included in cluster samples. The perception of esthetics was the exposure of our study and it was measured by the Arabic version of the Orofacial Esthetic Scale (OES-Ar). Gingivitis was the outcome of our study and it was measured by the gingival index of the Löe & Silness. The inter-examiner agreement was determined using kappa statistics (0.6) with a 95% confidence interval (CI) based on WHO examination form. SPSS version 21 was used for the statistical analysis. Results: There was a significant correlation (p = 0.002) between perception of esthetic and gingival index. The correlation was negative and weak. There was a significant difference in esthetic perception and gingival index for both genders. The correlation between age and gingival index was −0.086 (p = 0.000) which was significant, however, correlation was negative and weak. Conclusions: Gingivitis can be affected by the individual's perception of esthetic.